2018
DOI: 10.1038/s41598-018-32241-4
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle metabolomics and blood biochemistry analysis reveal metabolic changes associated with dietary amino acid supplementation in dairy calves

Abstract: The effects of different amino acid (AA) supplementations of milk protein-based milk replacers in pre-ruminant calves from 3 days to 7 weeks of age were studied. Animals were divided into 4 groups: Ctrl) Control group fed with milk protein-based milk replacer without supplementation; GP) supplementation with 0.1% glycine and 0.3% proline; FY) supplementation with 0.2% phenylalanine and 0.2% tyrosine; MKT) supplementation with 0.62% lysine, 0.22% methionine and 0.61% threonine. For statistical analysis, t-test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…These results indicated that metabolite signatures could be utilized as indices not only in feeding-originated beef quality but also in animal welfare and authentication. In other studies, the effects of dietary amino acids and mate extract administration on beef were also investigated by NMR approaches followed by PCA [21,22]. Biopsy semitendinosus muscle samples of dairy calves fed protein-based milk replacer at 7 weeks of age were classified by amino acid supplementation [21].…”
Section: Animal Feedingmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that metabolite signatures could be utilized as indices not only in feeding-originated beef quality but also in animal welfare and authentication. In other studies, the effects of dietary amino acids and mate extract administration on beef were also investigated by NMR approaches followed by PCA [21,22]. Biopsy semitendinosus muscle samples of dairy calves fed protein-based milk replacer at 7 weeks of age were classified by amino acid supplementation [21].…”
Section: Animal Feedingmentioning
confidence: 99%
“…In other studies, the effects of dietary amino acids and mate extract administration on beef were also investigated by NMR approaches followed by PCA [21,22]. Biopsy semitendinosus muscle samples of dairy calves fed protein-based milk replacer at 7 weeks of age were classified by amino acid supplementation [21]. Additionally, in a study of feedlot Nellore cattle, the dietary addition of mate extract, one of the antioxidant additives administered to broiler chickens, resulted in increased content of IMP, creatine, carnosine, and conjugated linoleic acid in the LT muscle, and some of these were in a dose-dependent manner [22].…”
Section: Animal Feedingmentioning
confidence: 99%
“…The use of these two omics technologies has been crucial in dairy sciences and several proteins and metabolites have been associated to specific study topics. Thus, studies about tolerance to seasonal weight loss in dairy goats (Hernández-Castellano et al ., 2015), insulin resistance in transition dairy cows (Zachut, 2015), response to seasonal heat stress in late pregnant dairy cows (Zachut et al ., 2017) and amino acid composition of milk replacer on muscle metabolites (Yu et al ., 2018) have been published over the last few years. Moreover, as newborn survival is an important factor affecting fitness, assessment of colostrum quality and intake represents an important area of investigation in both large and small ruminants (Banchero et al ., 2015; Buczinski and Vanderveerd, 2016).…”
Section: Emergence Of New Analytical Technologies To Improve Dairy Prmentioning
confidence: 99%
“…Biopsies were obtained from the semitendinosus muscle as previously described [11] and kept at −80 °C until further analysis. Prior to Omics assays, frozen muscle tissues were ground into a fine powder with mortar and pestle in liquid nitrogen and at least two 0.5 g aliquots were made and kept in a 15 ml polypropylene vial at -80 °C.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Methods, reagents and intra-assay CV (%) were previously reported [12]. Plasma AA were determined by HPLC as described [11] with some modifications. Briefly, an Elite LaChrom (Hitachi, Tokyo, Japan) equipped with an UV detector (Hitachi L-24200, Tokyo, Japan) with a Novapak C18 column (300 mm x 3.9 mm) from Waters (Milford, MA, USA) were used.…”
Section: Serum Clinical Chemistry and Plasma Aamentioning
confidence: 99%